Complementing the Sugar Code: Role of GAGs and Sialic Acid in Complement Regulation - Langford-Smith, Alex; Day, Anthony J.; Bishop, Paul N.; Clark, Simon J. (Frontiers in Immunology, 2015)
Sugar molecules play a vital role on both microbial and mammalian cells, where they are involved in cellular communication, govern microbial virulence and modulate host immunity and inflammatory responses. The complement cascade, as part of a host’s innate immune system, is a potent weapon against invading bacteria but has to be tightly regulated to prevent inappropriate attack and damage to host tissues. A number of complement regulators, such as factor H and properdin, interact with sugar molecules, such as glycosaminoglycans and sialic acid, on host and pathogen membranes and direct the appropriate complement response by either promoting the binding of complement activators or inhibitors. The binding of these complement regulators to sugar molecules can vary from location to location, due to their different specificities and because distinct structural and functional subpopulations of sugars are found in different human organs, such as the brain, kidney and eye. This review will cover recent studies that have provided important new insights into the role of glycosaminoglycans and sialic acid in complement regulation and how sugar recognition may be compromised in disease